Demographic and Clinical Characteristics of 907 Cases with Naltrexone Intoxication; a 14-Year Cross-Sectional Study - Rahimi, Mitra; Kargar, Alireza; Hazegh Fetratjoo, Delara; Hosseini, Sayed Masoud; Mahdavinejad, Arezou; Shadnia, Shahin (Archives of Academic Emergency Medicine, 2022)
Introduction: Opioids have been the leading cause of death from poisoning in Iran for several years. This study aimed to evaluate the clinical and para-clinical presentations of naltrexone intoxication, its toxic dose, and its epidemiological properties. Methods: This retrospective cross-sectional study was conducted on medical records of patients presenting to Toxicology Department of Loghman Hakim Hospital, Tehran, Iran, following naltrexone intoxication, from 2002 to 2016. Patients’ demographic and laboratory data, clinical signs, supposed ingested dose, and intent of naltrexone consumption were collected, analyzed, and then interpreted. Results: 907 patients with the mean age of 36.6 ±11.7 years were evaluated (94.3% male). The mean amount of naltrexone consumed by the intoxicated patients reported in the medical records was 105.8 ± 267.8 mg. One hundred thirty patients (14.3%) used naltrexone to treat substance use disorder. Two hundred eighty-seven poisoned patients (31.6%) were current opium users who intentionally or unintentionally used naltrexone concomitantly. The most common symptoms observed in these patients were agitation (41.8%), vomiting (16.4%), and nausea (14.8%). Among patients with naltrexone poisoning, 25 patients were intubated (2.8%), and three passed away. Aspartate aminotransferase (AST) levels were significantly higher in patients intoxicated with naltrexone who needed intubation (p = 0.02). Conclusion: The probability of intubation of cases with naltrexone intoxication was associated with AST elevation. It seems that, the number of intensive care unit (ICU) admissions and mortality rates are not high among these patients.